LIMD1 is more frequently altered than RB1 in head and neck squamous cell carcinoma: clinical and prognostic implications - Ghosh, Susmita (BioMed Central, 2010)
INTRODUCTION: To understand the role of two interacting proteins LIMD1 and pRB in development of head and neck squamous cell carcinoma (HNSCC), alterations of these genes were analyzed in 25 dysplastic head and neck lesions, 58 primary HNSCC samples and two HNSCC cell lines. METHODS: Deletions of LIMD1 and RB1 were analyzed along with mutation and promoter methylation analysis of LIMD1. The genotyping of LIMD1 linked microsatellite marker, hmlimD1, was done to find out any risk allele. The mRNA expression of LIMD1 and RB1 were analyzed by Q-PCR. Immunohistochemical analysis of RB1 was performed. Alterations of these genes were correlated with different clinicopathological parameters. RESULTS: High frequency [94% (78/83)] of LIMD1 alterations was observed in the samples studied. Compare to frequent deletion and methylation, mutation of LIMD1 was increased during tumor progression (P = 0.007). Six novel mutations in exon1 and one novel intron4/exon5 splice-junction mutation were detected in LIMD1 along with a susceptible hmlimD1 (CA)(20 )allele. Some of these mutations [42% (14/33)] produced non-functional proteins. RB1 deletion was infrequent (27%). Highly reduced mRNA expression of LIMD1 (25.1 ± 19.04) was seen than RB1 (3.8 ± 8.09), concordant to their molecular alterations. The pRB expression supported this data. Tumors with LIMD1 alterations in tobacco addicted patients without HPV infection showed poor prognosis. Co-alterations of these genes led the worse patients' outcome. CONCLUSIONS: Our study suggests LIMD1 inactivation as primary event than inactivation of RB1 in HNSCC development.